ANALISIS DISIPLIN KERJA PEGAWAI PADA BIDANG PENDAFTARAN PENDUDUK DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL (DISDUKCAPIL) KARAWANG - Indah Yunengsih (MANAJEMEN DEWANTARA, 2026)
This research intends to analyze the level of work discipline among employees within the Population Registration Division of the Karawang Regency Population and Civil Registration Office and to determine the factors impacting it. This study applies a qualitative descriptive methodology through data collection via documentation, interviews, and observation. This study involved five informants consisting of the Head of the Population Registration Division, the Head of the General and Personnel Subdivision, and Population Registration Staff. Source triangulation was used as a validation method to strengthen the validity of the research results. Research shows that even if shared work discipline is good, employees demonstrate an understanding of work standards, compliance with regulations, a high level of alertness in service, and an ethical work culture. However, an increase in tardiness was found to be influenced by internal factors such as lack of rest time and personal readiness, as well as external factors such as traffic congestion, distance from home, and family matters. In conclusion, employees have demonstrated understanding and compliance with work standards, though there are yet obstacles in executing them regularly. Therefore, agencies need to adopt fines and grants balancedly to grow employee task discipline as a means to support productivity and effectiveness of public services, as well as optimize efficient management of working time.